Annual report 2017: CGIAR Research Program on Agriculture for Nutrition and Health - CGIAR Research Program on Agriculture for Nutrition and Health (CGIAR Research Program on Agriculture for Nutrition and Health, 2018)
A4NH is led by the International Food Policy Research Institute (IFPRI) and managed by a group that includes four other CGIAR Centers: Bioversity International, the International Center for Tropical Agriculture (CIAT), the International Institute of Tropical Agriculture (IITA), and the International Livestock Research Institute (ILRI); and two academic institutions: the London School of Hygiene & Tropical Medicine (LSHTM) and Wageningen University and Research (WUR).